Age-related alteration of arginase activity impacts on severity of leishmaniasis. - Ingrid Müller; Asrat Hailu; Beak-San Choi; Tamrat Abebe; Jose M Fuentes; Markus Munder; Manuel Modolell; Pascale Kropf (Public Library of Science (PLoS), 2008)
The leishmaniases are a group of vector-borne parasitic diseases that represent a major international public health problem; they belong to the most neglected tropical diseases and have one of the highest rates of morbidity and mortality. The clinical outcome of infection with Leishmania parasites depends on a variety of factors such as parasite species, vector-derived products, genetics, behaviour, and nutrition. The age of the infected individuals also appears to be critical, as a significant proportion of clinical cases occur in children; this age-related higher prevalence of disease is most remarkable in visceral leishmaniasis. The mechanisms resulting in this higher incidence of clinical disease in children are poorly understood. We have recently revealed that sustained arginase activity promotes uncontrolled parasite growth and pathology in vivo. Here, we tested the hypothesis that arginase-mediated L-arginine metabolism differs with age.The age distribution of patients with visceral or cutaneous leishmaniasis was determined in cohorts of patients in our clinics in endemic areas in Ethiopia. To exclude factors that are difficult to control in patients, we assessed the impact of ageing on the manifestations of experimental leishmaniasis. We determined parasite burden, T cell responses, and macrophage effector functions in young and aged mice during the course of infection.Our results show that younger mice develop exacerbated lesion pathology and higher parasite burdens than aged mice. This aggravated disease development in younger individuals does not correlate with a change in T helper cytokine profile. To address the underlying mechanisms responsible for the more severe infections in younger mice, we investigated macrophage effector functions. Our results show that macrophages from younger mice do not have an impaired capacity to kill parasites; however, they express significantly higher levels of arginase 1 than aged mice and promote parasite growth more efficiently. Thus, our results demonstrate that ageing differentially impacts on L-arginine metabolism and subsequent effector functions of physiologically distinct macrophage subsets.Here, we show that arginase-mediated L-arginine metabolism is modulated with age and affects the capacity of macrophages to express arginase; the increased capacity to upregulate this enzyme in younger individuals results in a more permissive environment for parasite growth, increased disease severity and pathology. These results suggest that the difference in arginase-mediated L-arginine catabolism is likely to be an important factor contributing to the increased incidence of clinical cases in children. Thus, targeting L-arginine metabolism might be a promising therapeutic strategy against leishmaniasis, especially in children and young adults.